2019
DOI: 10.1021/acs.analchem.8b05549
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Isotopic Characterization of Noble Metal Phase from Commercial UO2 Fuel

Abstract: We report elemental and isotopic analysis for the noble metal fission product phase found in irradiated nuclear fuel. The noble metal phase was isolated from three commercial irradiated UO 2 fuels by chemically dissolving the UO 2 fuel matrix, leaving the noble metal phase as the undissolved residue. Macro amounts of this residue were dissolved using a KOH + KNO 3 fusion and then chemically separated into individual elements for analysis by mass spectrometry. Though the composition of this phase has been previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…This study has also confirmed the observation by Pellegrini et al 36 that Te is a major fission product in these particles. The exact nature of the association of Te with the noble metal phase particles needs to be studied further.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study has also confirmed the observation by Pellegrini et al 36 that Te is a major fission product in these particles. The exact nature of the association of Te with the noble metal phase particles needs to be studied further.…”
Section: Discussionsupporting
confidence: 92%
“…Tellurium was consistently associated with the noble metal phase particles, and elemental analysis of a dissolved portion of the phase showed quantities around 5% of the particle. 36 These two studies (Pellegrini et al and this study) provide clear association of Te with the noble metal phase particles that had not been previously established in earlier studies. A line-scan across the particle showed evidence of chemical fractionation.…”
Section: Analysis Of Noble Metal Phase Particles In Cladding Linersupporting
confidence: 69%
See 1 more Smart Citation
“…This irradiation is substantially longer than typical in commercial reactor operations. Portions of this fuel were subsequently made available for study as 'Approved Testing Material 109' (henceforth, 'ATM-109'), which has also been characterized for various research purposes (e.g., Wolf et al, 2005;Buck et al, 2015;Pellegrini et al, 2019;Clark et al, 2020). Analyses of various subsamples of this material indicated radially averaged burnup in the range 61-78 GWd//ton (Wolf et al, 2005).…”
Section: Sample Acquisition and Analysismentioning
confidence: 99%
“…This irradiation is substantially longer than typical in commercial reactor operations. Portions of this fuel were subsequently made available for study as 'Approved Testing Material 109' (henceforth, 'ATM-109'), which has also been characterized for various research purposes (e.g., Wolf et al, 2005;Buck et al, 2015;Pellegrini et al, 2019;Clark et al, 2020). Analyses of various subsamples of this material indicated radially averaged burnup in the range 61-78 GWd//ton (Wolf et al, 2005).…”
Section: Sample Acquisition and Analysismentioning
confidence: 99%